WOMEN'S WORLD IN SHORT STORIES ON DUNIASANTRI.CO: A READING OF SANTRIWATI'S WORKS - Diah Haryanti, Novi; Fitriyah, Atiqotul; Pitaloka, Aprilia; Hudaa, Syihaabul; Rizky Utama, Virdika (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT This paper aims to examine the world of women in short stories writÂten by santriwati (female students) on duniasantri.co website, which was the first pioneer of student journalism with the concept of citizen journalism. There are 78% of short stories written by santri (male students) and only 22% of short stories written by santriwati. This gender-based contribution imbalance was appealing to study further. Using qualitative descriptive method to explore the santriwati short stories, this research analyzes five short stories in duniasantri.co written by santriwati. To strengthen the data and analysis, the researcher also conducted interviews with the santriwati authors. The study found that there were various themes such as matchmaking and marriage in pesantren, the search for identity, the longing for Ramadan and Lailatul Qadar, and patriarchy culture. These themes indicate that education in Islamic boarding schools produces female students with heterogeneous thinking. Therefore, it can be concluded that the world of women is not seen as uniform by santriwati. Keyword: duniasantri.co, Pesantren, Santriwati, Women's World. ABSTRAK Tulisan ini bertujuan untuk mengkaji dunia perempuan dalam cerpen-cerpen yang ditulis santriwati di website Duniasantri.co yang merupakan pelopor jurnalisme santri pertama berkonsep citizen journalism. Terdapat 78% cerpen ditulis oleh santri dan hanya 22% cerpen ditulis oleh santriwati. Ketimpangan komposisi tersebut menjadi daya tarik untuk melihat bagaimana kisah-kisah yang diproduksi oleh santriwati. Penelitian ini menggunakan metode deskrispi kualitatif dengan objek kajian cerpen-cerpen karya santriwati di duniasantri.co. Untuk memperkuat data dan analisis, peneliti juga melakukan wawancara dengan para penulis santriwati. Berdasarkan hasil analisis terhadap lima cerpen yang ditulis oleh santriwati di duniasantri.co memperlihatkan karakteristik tema yang beraÂgam seperti perjodohan dan pernikahan di pesantren, pencarian identitas para santriwati di pesantren, kerinduan terhadap bulan Ramadan dan Lailatul Qadar, serta budaya patriarki yang masih membelenggu peremÂpuan. Tema-tema tersebut memperlihatkan, pendidikan di pesantren menghasilkan santriwati dengan pemikiran beragam (heterogen). Dengan demikian dapat disimpulkan dunia perempuan tidak dilihat seragam oleh santriwati. Kata Kunci: Dunia Perempuan, duniasantri.co, Santriwati, Sastra Pesantren.